PELAKSANAAN KEBIJAKAN PEMERINTAH KOTA TANJUNGPINANG DALAM PEMENUHAN HAK PEKERJAAN BAGI PENYANDANG DISABILITAS - Shintia Shintia; Shahril Budiman; Neng Suryanti Nengsih (University of Muhammadiyah Malang, 2022)
In the implementation of tanjungpinang city regulation No. 4 of 2017 concerning the Implementation of The Rights of Persons with Disabilities there are still many that have not been done optimally such as the Local government should guarantee the recruitment process, acceptance, job training, work placement, work sustainability, and career development that is fair and without discrimination to people with disabilities but judging by the number of private parties and government agencies that do not want to employ disabilities. The purpose of this study is to find out the Implementation of Tanjungpinang City Regulation No. 4 of 2017 on The Implementation of The Rights of Persons with Disabilities (Study on The Fulfillment of Employment Rights for People with Disabilities in Tanjungpinang City). In this study the theory used according to Van Meter and Van Horn (in Subarsono, 2011;99). In this study was taken a sample of 5 people. The data analysis technique used in this study is qualitative descriptive data analysis technique. Based on the results of the study, the policies has not run optimally because in fact people with disabilities do not get their rights in finding workers, this is because it is not supported by the local government itself, either facilities, coordination. The number of people working is considered inappropriate or unbalanced with people with disabilities in tanjungpinang city, the advice that can be submitted is as follows the need for coordination between the Office of Manpower and Social Services of Tanjungpinang City in the preparation of employment rights fulfillment programs for people with disabilities. There needs to be a derivative regulation in the form of mayor regulation in the implementation of the regulation on the Implementation of The Rights of Persons with Disabilities. There needs to be the establishment of a Disability Services Unit and then there should be public service facilities that are easily accessible to people with disabilities.